2017
DOI: 10.3389/fneur.2017.00523
|View full text |Cite
|
Sign up to set email alerts
|

Inner Retinal Dysfunction in the Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay

Abstract: The autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is associated with structural retinal abnormalities either directly visible on funduscopy or revealed by optical coherence tomography (OCT). Most patients with ARSACS have a whitish peripapillary appearance corresponding to a thickening of the peripapillary retinal nerve fiber layer. OCT has also shown an absence of the physiological foveal depression. Abnormal electroretinography (ERG) has previously been reported in only two cases, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…4 There are no reports of VA loss, reduced visual fields, or color vision changes in patients with autosomal recessive spastic ataxia of Charlevoix-Saguenay. 18 This is consistent with findings in our patient, who had normal vision.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 There are no reports of VA loss, reduced visual fields, or color vision changes in patients with autosomal recessive spastic ataxia of Charlevoix-Saguenay. 18 This is consistent with findings in our patient, who had normal vision.…”
Section: Discussionsupporting
confidence: 93%
“…9,10 Given these criteria, our patient had thickening in both eyes, with an average thickness of 180 µm in the right eye and 177 µm in the left eye. Peripapillary thickening of the RNFL has a specificity of 100% but reduced sensitivity in certain patient populations; for example, a study of Japanese patients with the disorder found no RNFL thickening on OCT. 18 Of 17 patients diagnosed with autosomal recessive spastic ataxia of Charlevoix-Saguenay in a British study, all patients were found to have RNFL thickening. 9 The authors thus defined this thickening as a hallmark of the disorder and a way to differentiate the disease from other causes of ataxia.…”
Section: Discussionmentioning
confidence: 98%
“…7 Autosomal recessive spastic ataxia of Charlevoix-Saguenay may be associated with fovea plana. 8 This case presents mild fovea plana corresponding to grade 1 in the grading scale proposed by Thomas et al 9 with absence of plexiform layers extrusion. Macular microcysts have also been described in ARSACS, but their pathological significance is yet to be determined.…”
Section: Discussionmentioning
confidence: 87%